Statistical Data Retrieval Technique in Astronomy Computational Physics - Ruben Cornelius Siagian; Pandu Pribadi; Goldberd Harmuda Duva Sinaga; Arip Nurahman; Budiman Nasution (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Computational astronomy is a very important branch in today's era, where physicists or researchers can use computers to process statistics in astronomical physics. researchers can process abstract data from raw data and can convert data into data visualizations. Computational physics astronomy is a sophisticated and well-established method, this branch of science can provide and process data, solve complex problems, and is very helpful for statisticians and computer scientists. Astronomical physicists have many problems, among others; there is a problem that is hierarchical, and complex, so that this paper will provide a basis for methods for optimizing methods in processing statistical data on physics. The author's hope is that astronomical physicists can perform an important and effective processing of astronomical data optimally and effectively.